Catalytic power of a pandemic: on enacting agency in professional higher education spaces through communities of practice - De Klerk, Danie (HELTASA (Higher Education Learning and Teaching Association of Southern Africa), 2022)
This chapter critically interrogates the agential metamorphosis the author experienced over an 18-month period during the Covid-19 pandemic, by means of numerous diverse communities of practice (CoPs). As a mid-career academic occupying a middle-management leadership position in a faculty, at a large, research-intensive public university in South Africa, the author first outlines the numerous professional tensions that characterise the dual roles he holds in the faculty. Underpinned by Social Realist principles and Archer’s (1995, 2000, 2005) notions about morphogenesis, the chapter explores the temporal interplay between structures (in the form of CoPs) and agency (in the form of the author’s agential metamorphosis). The chapter postulates that the Covid-19 pandemic served as a catalyst in this interplay, according the author unique opportunities to become part of numerous diverse CoPs that evolved organically during this time. Synergistic with this evolution, was that of the author’s awareness of his own agential potential and the intentionality with which he came to enact agency in the professional spaces he occupies. By linking the CoPs to four professional meta-identities, the chapter allows for critical reflections on how each CoP contributed in unique but interconnected ways to the author’s agential metamorphosis, catalysed by the pandemic. The chapter concludes by making recommendations on how higher education stakeholders can use CoPs and critical reflection about agential potential as ways of eliciting and enacting agency in their own professional spaces.
Keywords: Agency; Community of practice; Critical reflection; Morphogenesis; Morphogenetic framework; Morphogenetic cycle; Social realism; SDG-10: Reduced inequalities